POLITIK LUAR NEGERI ARAB SAUDI DAN AJARAN SALAFI-WAHABI DI INDONESIA - Hasbi Aswar (The Indonesian Islamic Studies and International Relations Association (Insiera), 2016)
This article aims to explore the role of Saudi Arabian Foreign Policy in disseminating Wahhabi doctrines in Indonesia. Islam is one important aspect in Saudi Arabian Foreign Policy since its beginning in 18th century until nowadays.In early Saudi Kingdom, its foreign policy focused on expansion of its power and spread the Wahhabi doctrines in the region of Arabia. This expansive policy resulted long conflict between Saudi Kingdom and Ottoman Empire. In modern Saudi Arabia Kingdom, Islam in Saudi Arabian Foreign Policy can be seen through its big role to support and contribute Islamic Da’wah (Preaching of Islam) in many ways, such as by education assistance and building Islamic Center in many countries. However, the expansion of Saudi Arabia Islamic da`wah remains controversy between many observers. Some contend that Islamic Da`wah based on Wahhabi doctrines can produce extrimism or radicalism becoming threat to world peace and security.